Decision Making in Interventional Oncology: Ablative Options in the Lung - Lee, Kyungmouk Steve; Erinjeri, Joseph P. (Seminars in Interventional Radiology, 2017)
Image-guided ablation is safe and effective for the treatment of both primary and metastatic tumors in the lung. This article reviews the three most commonly used ablative options: radiofrequency ablation, microwave ablation, and cryoablation. We describe the advantages of each ablation modality in the lung and how to choose the most appropriate ablation device based on patient and tumor characteristics. The optimal technique for lung ablation is discussed and technical tips for improving clinical outcome are described.
Keywords: lung ablation; image-guided ablation; lung cancer; interventional radiology